Evaluation of Emotional Divorce in Male Patients with Urethral Distraction Defect in a Referral Center - Allameh, Farzad; Hosseini, Jalil; Ajori, Ladan; Faraji, Saba; Hojjati, Seyyed Ali; Alinejad Khorram, Amir (Archives of Men’s Health, 2023)
Background: Emotional divorce is the first stage of divorce in which the marital relationship deteriorates and the couple’s relationship lacks love and affection. Given that the family is one of the foundations of the society, emotional divorce can have devastating effects on society and negative effects on family members. Therefore, it is essential to study this issue. Methods: Patients with Pelvic Fracture Urethral Distraction Defect (PFUDD) admitted consecutively to Shohada-e-Tajrish Hospital (Tehran, Iran) from May 2020 to May 2021 were enrolled in the study. In this study all patients were evaluated by two questionnaires: Gottman emotional divorce questionnaire to assess the patient’s marital status, and the International Index of Erectile Function (IIEF-5) questionnaire to assess the patient’s sexual situation. Results: The mean score for the IIEF-5 scores in the case and control groups were 18.32 and 21.04, respectively. The mean Gottman Scores in the case and control groups were 3.84 and 2.12, respectively. There was no significant difference between IIEF-5 and Gottman Scores between the two groups. Conclusions: Considering the lack of differences between the two groups, it can be inferred that the effect of the spiritual and emotional dimension in strengthening marriage was more than the physical dimension. When a man encounters a physical problem, his wife will play a supportive role and seek to strengthen relationship and solve problems.